2017
DOI: 10.3917/rhmc.644.0025
|View full text |Cite
|
Sign up to set email alerts
|

Niveau de vie et révolution des objets dans la France d’Ancien Régime. Meaux et ses campagnes aux XVII e et XVIII e  siècles

Abstract: En exploitant le corpus des inventaires après décès réuni par Micheline Baulant pour la région de Meaux aux XVII e et XVIII e siècles, l’évolution du niveau de vie des populations de la ville et de sa campagne a pu être mesurée. Elle témoigne d’une stagnation au cours du XVII e siècle et d’une forte progression pendant le siècle suivant, ce qui permet de confirmer la réalité d’une « révolution des objets » ou d’une consumer revolution en milieu rural dans la France du XVIII e siècle. Mais ce changement ne semb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…A recent study, again at the micro-level, complements the idea that the demographic transition was indeed led by better economic conditions. Using a unique, comprehensive household-level data set for a single French village from 1730 to 1895, Blanc and Wacziarg (2019) found that the rise of life expectancy (in the middle eighteenth century) preceded the fall of fertility by several decades, confirming the idea that the French demographic transition was led by an increase in living standards (Béaur 2017).…”
Section: More Models Are Neededmentioning
confidence: 92%
“…A recent study, again at the micro-level, complements the idea that the demographic transition was indeed led by better economic conditions. Using a unique, comprehensive household-level data set for a single French village from 1730 to 1895, Blanc and Wacziarg (2019) found that the rise of life expectancy (in the middle eighteenth century) preceded the fall of fertility by several decades, confirming the idea that the French demographic transition was led by an increase in living standards (Béaur 2017).…”
Section: More Models Are Neededmentioning
confidence: 92%
“…A recent study, again at the microlevel, complements the idea that the demographic transition was indeed led by better economic conditions. Using a unique, comprehensive household-level data set for a single French village from 1730 to 1895, Blanc and Wacziarg (2019) found that the rise of life expectancy (in the middle eighteenth century) preceded the fall of fertility by several decades, confirming the idea that the French demographic transition was led by an increase in living standards (Béaur 2017).…”
Section: R24 the Behavioral Constellation Of Affluence And Its Rolementioning
confidence: 89%
“…It shows that the social groups comparable with our treballadors ( journaliers and vignerons ) were those less favoured by the eighteenth-century ‘revolution of objects’. However, the standard of living index based on their inventories grew by around 60 per cent between 1651–1700 and 1751–90, and by 35 per cent between 1701–50 and 1751–90 (Béaur, 2017: 38–41). These figures are similar to the rise in the number of items owned by treballadors.…”
Section: Comparing Catalonia With North-western Europementioning
confidence: 99%
“…This point has always proved controversial, even for northwestern Europe, where de Vries situated the industrious revolution, and is even more so when referring to the rural world. 2 Another problematic aspect of the debate regarding the industrious revolution is the lack of dialogue between historiographies (Clunas, 1999;Béaur, 2017), highlighted by the arguments in favour of excluding the Mediterranean area, which we shall discuss through the example of Catalonia. Leaving aside the issue of family structures, which we shall not address here, 3 it is surprising that de Vries ignores something that the historiography referring to southern Europe highlighted some time ago: that specialisationand therefore the growing link with the marketis one of the most striking features of agricultural growth in the Mediterranean area (Vilar, 1964-8: III, 185).…”
Section: Introductionmentioning
confidence: 99%